A pilot study of marking accuracy and mental workload as measures of OSCE examiner performance. Issue 1 (December 2016) - Byrne, Aidan; Soskova, Tereza; Dawkins, Jayne; Coombes, Lee
Abstract Background The Objective Structured Clinical Examination (OSCE) is now a standard assessment format and while examiner training is seen as essential to assure quality, there appear to be no widely accepted measures of examiner performance. Methods The objective of this study was to determine whether the routine training provided to examiners improved their accuracy and reduced their mental workload. Accuracy was defined as the difference between the rating of each examiner and that of an expert group expressed as the mean error per item. At the same time the mental workload of each examiner was measured using a previously validated secondary task methodology. Results Training was not associated with an improvement in accuracy (p  = 0.547) and that there was no detectable effect on mental workload. However, accuracy was improved after exposure to the same scenario (p  < 0.001) and accuracy was greater when marking an excellent compared to a borderline performance. Conclusions This study suggests that the method of training OSCE examiners studied is not effective in improving their performance, but that average item accuracy and mental workload appear to be valid methods of assessing examiner performance.